Service : a Navy SEAL at war - Luttrell, Marcus (Little, Brown and Co., 2012)
"Navy SEAL Marcus Luttrell returned from his star-crossed mission in Afghanistan with his bones shattered and his heart broken. So many had given their lives to save him-- and he would have readily done the same for them. As he recuperated, he wondered why he and others, from America's founding to today, had been willing to sacrifice everything-- including themselves-- for the sake of family, nation, and freedom. In Service, we follow Marcus Luttrell to Iraq, where he returns to the battlefield as a member of SEAL Team 5 to help take on the most dangerous city in the world, Ramadi, the capital of war-torn Al Anbar Province. There, in six months of high-intensity urban combat, he would be part of what has been called the greatest victory in the history of U.S. Special Operations forces. We also return to Afghanistan and Operation Redwing, where Luttrell offers powerful new details about his miraculous rescue. Throughout, he reflects on what it really means to take on a higher calling, about the men he's seen lose their lives for their country, and the legacy of those who came and bled before."--Dust jacket.